Phosphite-Catalyzed C-H allylation of azaarenes via an enantioselective [2,3]-Aza-wittig rearrangement - Motaleb, Abdul; Rani, Soniya; Das, Tamal; Gonnade, Rajesh G.; Maity, Pradip (Angewandte Chemie-International Edition, 2019)
A phosphite-mediated [2,3]-aza-Wittig rearrangement has been developed for the regio- and enantioselective allylic alkylation of six-membered heteroaromatic compounds (azaarenes). The nucleophilic phosphite adducts of N-allyl salts undergo a stereoselective base-mediated aza-Wittig rearrangement and dissociation of the chiral phosphite for overall C-H functionalization of azaarenes. This method provides efficient access to tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems, tolerating a broad variety of substituents on both the allyl part and azaarenes. Catalysis with chiral phosphites is also demonstrated with synthetically useful yields and enantioselectivities.

Phosphite mediated asymmetric N to C migration for the synthesis of chiral heterocycles from primary amines - Rani, Soniya; Dash, Soumya Ranjan; Bera, Asish; Alam, Md Nirshad; Vanka, Kumar; Maity, Pradip (Chemical Science, 2021)
A phosphite mediated stereoretentive C-H alkylation of N-alkylpyridinium salts derived from chiral primary amines was achieved. The reaction proceeds through the activation of the N-alkylpyridinium salt substrate with a nucleophilic phosphite catalyst, followed by a base mediated [1,2] aza-Wittig rearrangement and subsequent catalyst dissociation for an overall N to C-2 alkyl migration. The scope and degree of stereoretention were studied, and both experimental and theoretical investigations were performed to support an unprecedented aza-Wittig rearrangement-rearomatization sequence. A catalytic enantioselective version starting with racemic starting material and chiral phosphite catalyst was also established following our understanding of the stereoretentive process. This method provides efficient access to tertiary and quaternary stereogenic centers in pyridine systems, which are prevalent in drugs, bioactive natural products, chiral ligands, and catalysts.

Organophosphites: an addition to the arsenal of organocatalysts - Baral, Nilofar; Rani, Soniya; Saikia, Pinku; Maity, Pradip (European Journal of Organic Chemistry, 2023)
Organophosphites are nucleophilic in nature and can act as a good leaving group owing to the stability of the phosphite anion. This dual reactivity makes them good candidates for nucleophilic organocatalysis. However, phosphites were introduced only in 2004 as the umpolung catalyst for acylsilane substrates utilizing sequential Brook rearrangements. Very recently, phosphites have been reported to catalyze aza-rearrangements and radical reactions. In this review, we discuss the reactivity parameters to understand its lack of use, as well as the potential for catalysis.
Keywords: acylradical; azaacyl equivalent; cylanion; organocatalysis; phosphite

Phosphite mediated molecular editing via switch to meta-C-H alkylation of isoquinolines: emergence of a distinct photochemical [1,3] N to C rearrangement - Rani, Soniya; Ray, Anuj Kumar; Dewangan, Devendra Kumar; Patil, Nita Aruna Ramchandra; Aarthika, M.; Paul, Ankan; Maity, Pradip (Chemical Science, 2025)
The isoquinoline core is present in one of the largest subsets of bioactive natural products. The multifunctional isoquinoline core exerts diverse bioactivity, resulting in the development of numerous isoquinoline-based drugs and molecules that are currently under clinical trials. We developed a new approach for phosphite-mediated [1,2] alkyl migration for an overall ortho-C-H alkylation via N-alkylation of isoquinoline. Tuning the phosphite-mediated protocol to switch the site selectivity would expedite direct and diverse multi-C-H bond functionalization. We report a new approach starting with a simple N-alkylation of isoquinoline with sterically and electronically diverse alkyl bromides for their phosphite-mediated photochemical [1,3] N to C rearrangement followed by a rearomatization sequence that leads to meta-C-H (C4) alkylation. Combined experimental and computational studies unveiled the emergence of an unprecedented C-N bond cleavage pathway from the singlet excited state of the enamine-type intermediate. Our radical bond-cleavage pathway favors substituted alkyl group migration that complements the recently successful meta-alkylation methods with smaller and more reactive electrophiles. This switch in site selectivity via tuning the phosphite-mediated protocol resulted in sequential C-H difunctionalization of isoquinoline including regiodivergent ortho, meta-dialkylations of isoquinolines.